2007
DOI: 10.1097/qad.0b013e3280b0774a
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the clinical, immunological and virological parameters of HIV-infected patients treated with HAART

Abstract: Women have more favourable clinical and viroimmunological patterns than men both at baseline and during antiretroviral treatment. Sex has a small but significant influence on the clinical and laboratory outcomes of HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
88
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 38 publications
20
88
1
3
Order By: Relevance
“…In two similar studies from rural Uganda, women were more likely to have a lower mortality than men as well a higher rate of viral suppression, although the findings did not quite reach statistical significance [10,34]. In countries where there is considerably more data on the relationship between sex and HAART outcomes, most studies have found no sex differences in response to treatment [14,15] with a few showing more favorable responses in women [35,36]. Previous studies have identified age [37,38] and low baseline CD4 counts [39] as risk factors for incomplete CD4 cell recovery.…”
Section: Discussionmentioning
confidence: 93%
“…In two similar studies from rural Uganda, women were more likely to have a lower mortality than men as well a higher rate of viral suppression, although the findings did not quite reach statistical significance [10,34]. In countries where there is considerably more data on the relationship between sex and HAART outcomes, most studies have found no sex differences in response to treatment [14,15] with a few showing more favorable responses in women [35,36]. Previous studies have identified age [37,38] and low baseline CD4 counts [39] as risk factors for incomplete CD4 cell recovery.…”
Section: Discussionmentioning
confidence: 93%
“…1,7 Some studies indicate that women have higher rates of clinical progression to acquired immunodeficiency syndrome (AIDS) and death while others have suggested the opposite. 1,2,8 Differential access to care for women between studies may be an important factor explaining these discrepancies.…”
Section: Dovepressmentioning
confidence: 99%
“…1,7 Some studies indicate that women have higher rates of clinical progression to acquired immunodeficiency syndrome (AIDS) and death while others have suggested the opposite. 1,2,8 Differential access to care for women between studies may be an important factor explaining these discrepancies. 1,2,8 Many women with HIV report high rates of poverty, are often depended on for care of children or family members, and may show a reluctance to take medication in public due to denial or fear of disclosure which may lead to compromised self-care, access to care, and response to treatment.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations